Clinical characteristics and preoperative outcomes in neonates with severe congenital heart disease at Hue Central Hospital - Do , Ho Tinh Tam; Nguyen , Cong Loi; Hoang , Mai Linh; Nguyen , Phuc Thu Trang; Nguyen , Nom; Nguyen , Thi Thao Trinh (Tạp chí Y Dược Huế, 2025)
Background: Approximately 25% of congenital heart disease (CHD) cases present symptoms during the neonatal period. These cases are classified as critical CHD, requiring immediate medical intervention or treatment. Preoperative stabilization plays a pivotal role in determining the prognosis, particularly for neonates. Subjects and Methods: This cross-sectional descriptive study with longitudinal follow-up included 39 neonates diagnosed with critical CHD via Doppler echocardiography at Hue Central Hospital from July 2022 to April 2023. Results: Ductal-dependent CHD was the most prevalent, accounting for 56.4% of cases, with 41% classified as ductal-dependent pulmonary circulation CHD. The most common clinical manifestations among neonates were cyanosis (51.3%) and heart murmur (46.2%). Prostaglandin therapy to maintain ductal patency was administered in 35.9% of cases. The mortality rate during preoperative stabilization was 25.6%. Risk factors associated with preoperative mortality in neonates with critical CHD included: Birth weight < 2500 grams (OR = 4.71, 95% CI: 1.03–21.65, p < 0.05); Invasive mechanical ventilation (OR = 23.62, 95% CI: 2.56–217.7, p < 0.05; Heart failure treatment (OR = 8.88, 95% CI: 1.56–50.5, p < 0.05); Inotropic support (OR = 8.67, 95% CI: 1.55–48.5, p < 0.05). Conclusions: Preoperative mortality risk in neonates with critical CHD is significantly increased by low birth weight (< 2500 grams), the need for invasive mechanical ventilation, heart failure treatment, and inotropic support.